Walking through Apertures: Do You Know What You are Doing during Body-Scaled Action?. (May 2013) - Keizer, Anouk; De Bruijn, Suzanne E M; Smeets, Monique A M; Dijkerman, H Chris; Postma, Albert
We investigated whether body-scaled action is influenced by awareness of task performance. Participants walked through apertures varying in size. Awareness of performing the action was manipulated by asking half of the participants to concurrently perform a haptic memory task. Distracted participants showed a smaller maximum amount of shoulder rotation at A/S crit . Walking through apertures thus seems a rather automatic/uniform process regarding action planning, but being distracted from performing the action appears to influence how the action is performed, and may increase its efficiency.